INTEGRATING THE ARCTIC INTO THE BELT AND ROAD INITIATIVE: ECONOMIC INTERACTIONS BETWEEN CHINA AND RUSSIA - Gapon, Maksim (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2024)
This article delves into the intricate web of Sino-Russian cooperation within the Arctic, spotlighting the synergistic ventures like the Yamal LNG project as emblematic of broader collaboration in energy, infrastructure development, and geopolitical strategy. It outlines China's proactive stance in leveraging Arctic resources and the Northern Sea Route (NSR) to diversify its energy supply and integrate this polar pathway into its monumental "Belt and Road" initiative. Despite geographical remoteness, China's burgeoning interest in Arctic affairs, primarily driven by economic, geopolitical, and environmental objectives, underscores a strategic alignment with Russia's Arctic dominion. However, this partnership navigates through a spectrum of collaborative and contentious dynamics, particularly around Arctic governance, environmental stewardship, and the exploitation of hydrocarbon resources. While Russia gains investment and technological prowess, enhancing its sovereignty over Arctic navigation and resource utilization, China secures a vital energy lifeline and asserts its global maritime ambitions. Nonetheless, divergent views on Arctic governance and environmental policies pose challenges to this alliance. The article posits that despite these ideological divergences, the mutual benefits of Sino-Russian cooperation in the Arctic will likely foster a stronger, more integrated partnership, potentially reshaping Arctic geopolitics and global energy markets.